Variable-Speed PICO Hydel Energy Storage with Synchronverter Control to Emulate Virtual Inertia in Autonomous Microgrids - Vasudevan K.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Control system analysis; Eigenvalues and eigenfunctions; Energy storage; MATLAB; Stochastic systems; System stability; Time domain analysis; Vector control (Electric machinery); Autonomous microgrids; Closed loop transfer function; Eigenvalue analysis; Operation and maintenance; Periodic maintenance; Steady state errors; Stochastic behavior; Time-domain simulations; Microgrids